To use or not to use teenage Afrikaans in HIV prevention messages directed at Afrikaans teenagers in Pretoria - Saal, Elvis Ockert (Stellenbosch Papers in Linguistics Plus, 2012)
The high HIV prevalence among young people makes them a prime target for HIV prevention campaigns, such as South Africa’s “loveLife” campaign. One way to deliver document-mediated HIV messages directed at the youth is to use a language style to which they can relate. Drawing on the Communication Accommodation Theory and Language Expectancy Theory it is argued that teenagers are more likely to view the writer and the teenage variety favourably if they identify with the teenage variety in the print media. In this study two teenage slang versions of the same HIV message were examined. One version was an English teenage variety (hereafter the “loveLife variety”) as used by loveLife in the print media.  The other version was a teenage Afrikaans constructed by the Afrikaans teenagers themselves (hereafter “authentic teenage Afrikaans”). These two teenage varieties were not only compared to each other, but also to a standard Afrikaans version of the message. Two authentic teenage Afrikaans varieties – clearly running along the previous racial lines of “coloured” and “white” – were identified. This study indicates a generally unfavourable reaction to the (English) loveLife variety by both the Coloured Afrikaans and White Afrikaans teenage groups. The Coloured Afrikaans teenagers viewed their authentic teenage Afrikaans (and the standard Afrikaans) very favourably and appropriate for HIV health communication. White Afrikaans teenagers viewed the use of their authentic teenage Afrikaans in document-mediated HIV messages as highly inappropriate.